The Effect of Augmented Reality Media on Elementary School Students' Understanding of the Solar System Concept - Hesti Wulandari; Supriadi; Mubarok Somantri (Jurnal Profesi Guru Indonesia, 2026)
Comprehending astronomical concepts, such as the solar system, requires high spatial visualization and abstract reasoning, which elementary school students often struggle to develop through static, two-dimensional textbook illustrations. While digital interventions are expanding, empirical insights regarding how Augmented Reality (AR) media can structurally bridge the gap between concrete perception and abstract macro-scientific concepts in early science education remain limited. This study aims to test the effect of augmented reality media on the understanding of the concept of the solar system in elementary school students. Employing a quantitative quasi-experimental design, this study involved 60 sixth-grade students, divided into an experimental class (n = 30, utilizing AR-based media) and a control class (n = 30, utilizing conventional instruction). Quantitative data were gathered via a validated conceptual understanding test and evaluated using descriptive metrics (mean, standard deviation, and learning completeness percentages) alongside paired and independent sample t-tests. The empirical outcomes reveal that AR media exerts a profoundly positive and statistically significant effect on students' conceptual understanding of the solar system. The experimental cohort achieved a vastly superior post-test mean score (92.37) compared to the control group (69.74). Furthermore, a lower standard deviation in the experimental group indicated more equitable knowledge distribution among students, complemented by a staggering 94.02% learning completeness rate against the control group's mere 75.43% (p < 0.05). Consequently, AR media serves as a potent pedagogical alternative to mitigate low conceptual comprehension in elementary science. Beyond classroom-level performance, these findings provide critical empirical baseline data for educational tech-developers to design interactive, three-dimensional spatial environments that make complex scientific phenomena accessible to young minds.